Hubungan antara Status Gizi dengan Kejadian Anemia pada Balita - Hapzah Hapzah; Sry Agusti Putri (Politeknik Kesehatan Kemenkes Mamuju, 2018)
Anemia is one of the main nutritional problem in Indonesia that can be suffered by all age groups ranging from infants, toddlers, school children, adolescents, adults, and elderly without exception. The aim of this study was to investigate the relationship between nutritional status with anemia in Toddlers. This study was conducted in Puskesmas Banggae II District East Banggae Majene with observational research with cross sectional study. There were 101 samples of mothers and toddlers taken by purposive sampling. Instrument in this study is dacing to weigh toddlers, questionnaires, and the hemoglobin test. Data were analyzed with chi-square test. The results study showed that there is a relationship between the nutritional status and the incidence of anemia in toddlers.